2000
DOI: 10.1023/a:1008130223190
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Normal human skin (NB1-RGB) cells were cultured in the presenceof polyinosinic and polycytidylic acids, diethylaminoethyldextran, cycloheximide and actinomycin D, which induced humaninterferon-beta. The simplest induction method, that requiredonly polyinosinic and polycytidylic acids and diethylaminoethyldextran was found to give the highest production ofinterferon-beta by the cells. The cell growth and productionof interferon-beta were investigated for NB1-RGB cellscultured on silk fibroin, poly(gamma-methyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…casting and LB methods, are a strong factor affecting cell growth. The concentration and production of interferon-¯per unit number of cells on the LB membranes were found to be higher than those on the cast membranes made of the same proteins except collagen [21].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…casting and LB methods, are a strong factor affecting cell growth. The concentration and production of interferon-¯per unit number of cells on the LB membranes were found to be higher than those on the cast membranes made of the same proteins except collagen [21].…”
Section: Introductionmentioning
confidence: 77%
“…collagen, bronectin, laminin, and vitronectin) [21,22]. The cell density of the broblast cells cultured on the LB membranes was found to be higher than that on the cast membranes made of bronectin, vitronectin, and collagen-blended membranes.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Silk fibroin is a natural polymer, produced by silk worms, that can be mass produced, and has been used as a textile fiber. Recently, many studies have reported silk use in nontextile fields, especially the biomedical field, as a substrate for enzyme immobilization,1, 2 bone‐compatible materials,3, 4 antithrombogenic material,5, 6 wound dressing,7, 8 drug carrier,9 and as a cell culture substrate 10–13. These findings indicate that silk fibroin will be a good basic component for new biomedical material development.…”
Section: Introductionmentioning
confidence: 99%
“…15 There have been very few prior studies of pure collagen or collagen/phospholipid LB films at vapor/liquid interfaces or on a solid support. 16,17 At 25 1C, a 0.1 wt% acetic solution of type I collagen (pH 3.0) was spread onto the surface of ultrapure water in a LB trough and successfully transferred onto silicon-coated glass by horizontal deposition. 16 Ghannam et al used a different method to incorporate collagen at the air/water interface by injecting a collagen solution in 0.5M acetic acid into the aqueous subphase with or without a phospholipid spread monolayer on the surface.…”
Section: Introductionmentioning
confidence: 99%